Waterlogging-induced changes in root architecture of germplasm accessions of the tropical forage grass Brachiaria humidicola - Cardoso Arango, Juan Andrés; Cruz Jiménez, J. de la; Rao, Idupulapati M. (Oxford University Press, 2014)
Waterlogging is one of the major factors limiting the productivity of pastures in the humid tropics. Brachiaria humidicola is a forage grass commonly used in zones prone to temporary waterlogging. Brachiaria humidicola accessions adapt to waterlogging by increasing aerenchyma in nodal roots above constitutive levels to improve oxygenation of root tissues. In some accessions, waterlogging reduces the number of lateral roots developed from main root axes. Waterlogging-induced reduction of lateral roots could be of adaptive value as lateral roots consume oxygen supplied from above ground via their parent root. However, a reduction in lateral root development could also be detrimental by decreasing the surface area for nutrient and water absorption. To examine the impact of waterlogging on lateral root development, an outdoor study was conducted to test differences in vertical root distribution (in terms of dry mass and length) and the proportion of lateral roots to the total root system (sum of nodal and lateral roots) down the soil profile under drained or waterlogged soil conditions. Plant material consisted of 12 B. humidicola accessions from the gene bank of the International Center for Tropical Agriculture, Colombia. Rooting depth was restricted by 21 days of waterlogging and confined to the first 30 cm below the soil surface. Although waterlogging reduced the overall proportion of lateral roots, its proportion significantly increased in the top 10 cm of the soil. This suggests that soil flooding increases lateral root proliferation of B. humidicola in the upper soil layers. This may compensate for the reduction of root surface area brought about by the restriction of root growth at depths below 30 cm. Further work is needed to test the relative efficiency of nodal and lateral roots for nutrient and water uptake under waterlogged soil conditions.